Effectiveness of Endoscopic Assisted Repair in Achilles Tendon Ruptures Compared to Percutaneous and Open Repair. Issue 1 (January 2022) - Ceccarini, Paolo; Marzano, Fabrizio; di Giacomo, Lorenzo; Rinonapoli, Giuseppe; Caraffa, Auro
Category: Arthroscopy; Sports; Trauma Introduction/Purpose: The Achilles tendon rupture is the third most common tendon's injury, with an incidence of 16- 18/100000. Various repair's techniques are described, however the best surgical treatment remains controversial. Our purpose was to evaluate the effectiveness of endoscopic assisted repair compared to traditional open repair and percutaneous technique. Methods: We carried out a prospective observational study in patient operated in our Orthopedic Department between 2017 and 2019. We enrolled 47 patients (40 M; 7F), with a mean age 42, 5 y.o with a mean follow up 32 months (12-60). The patients were divided in 3 groups according to the surgical procedures. Group A included 15 patients underwent to endoscopic assisted repair, Group B: 11 patients with percutaneous repair and group C 21 patients open repair. Demographic data, injury mechanisms, operation's time and technique were recorded. At final f-u complications, functional score (VAS, AOFAS AH, ATRS) were requested. The statistical analysis was performed with the t-student test. IRB approved. Results: The 78% of injuries occurred during recreational sport activities, with a majority during football amatorial matches. Operation's time was 42, 5 minutes for group A, 33, 3 for group B, 33, 5 for group C. Among group A, 1 patient developed a DVT. In group B no major complications were reported. In group C a patient suffered from infection with suture insufficiency. Ankle stiffness was reported in 25% of patients in group C. No axonotmesis or neurotmesis of suralis was observed; 16 of patients complained transitory paresthesia in the postoperative. The mean time to return to work's activity was 44, 2 days for group A, 35, 6 days for group B, and group C 91, 1 days, while the mean time to return to drive was in average 72, 1 days for group A, 66 days for group B, 92, 3 days for group C. ATRS was 79, 3 for group A, 87, 6 group B and 72, 75 group C. Conclusion: This technique is safe and achievable with low postoperative pain and complications, early return to activities, and satisfactory functional outcomes. Compared to standard percutane-ous repair, endoscopy-assisted repair of Achilles tendon ruptures may be useful because it ensures precise placement of sutures through the ten-don and real-time visualization of the gap. Further large-scale, randomized and prospective clinical trials must be the subject of future prospective study.